The The Effect of Seawater Use and Solution Composition on the Quality of Blackening Results - Purnama Sari, Dewi; Razzaq, Khazainnur; Ikhwan, Ris Muhammad Noval; Rahmayanti; Kamaludin; Pradana Putra, Eriek Aristya; Larasati, Tantra Diwa (Journal of Chemical Process Engineering, 2024)
The study of the use of seawater and the composition of blackening solutions on the quality of blackening results is essential in increasing the efficiency of raw materials and finding an adequate formulation in the blackening process. Blackening is a black oxide coating process that aims to increase metal resistance to corrosion and wear. This study uses seawater as a solvent with blackening solution raw materials consisting of NaOH and oxidizers with varying compositions. The parameters for testing the quality of blackening results include color testing using the visual matching method, image color picker application, and corrosion resistance testing using the weight loss method. The study results showed that seawater can be used as a solvent in making blackening solutions by providing a somewhat contrasting black color and slower corrosion rate compared to solutions without seawater. NaOH with a percentage of 50%, 70%, and 80% in the corrosion test showed an increase in corrosion resistance of 10%, 30%, and 40%, respectively, after immersion for 30 minutes at a temperature of 150°C. The resulting blackening process not only provides aesthetic value through black coating but also increases protection against material surface degradation. This research is expected to provide an alternative formulation of a blackening solution that is more environmentally friendly and economically efficient, mainly by utilizing seawater as a solvent. In addition, these results are expected to be the basis for further development in blackening applications on various materials for industrial needs.